2020
DOI: 10.3390/ijms21020510
|View full text |Cite
|
Sign up to set email alerts
|

Acid Stripping of Surface IgE Antibodies Bound to FcεRI Is Unsuitable for the Functional Assays That Require Long-Term Culture of Basophils and Entire Removal of Surface IgE

Abstract: Basophils are rare granulocytes and dysregulated functions of these cells are associated with several atopic and non-atopic allergic diseases of skin, respiratory system and gastrointestinal tract. Both cytokines and immunoglobulin E (IgE) are implicated in mediating the basophil activation and pathogenesis of these disorders. Several reports have shown that healthy individuals, and patients with allergic disorders display IgG autoantibodies to IgE and hence functional characterization of these anti-IgE IgG au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Here, we identified a discrete population of CCR3 high SSC low basophils in the blood of patients with ovarian cancer of diverse histologies and treatment histories ( Table S3 ). Like basophils from healthy and atopic individuals [ 60 , 61 , 62 , 63 , 64 ], the basophils from ovarian cancer patients also expressed cell-surface FcεRI, which were partly occupied by endogenous IgE. Having confirmed this basophil phenotype, we showed that patient-derived basophils were susceptible to activation by IgE- and non-IgE-mediated stimuli irrespective of prior anti-cancer therapy.…”
Section: Discussionmentioning
confidence: 53%
“…Here, we identified a discrete population of CCR3 high SSC low basophils in the blood of patients with ovarian cancer of diverse histologies and treatment histories ( Table S3 ). Like basophils from healthy and atopic individuals [ 60 , 61 , 62 , 63 , 64 ], the basophils from ovarian cancer patients also expressed cell-surface FcεRI, which were partly occupied by endogenous IgE. Having confirmed this basophil phenotype, we showed that patient-derived basophils were susceptible to activation by IgE- and non-IgE-mediated stimuli irrespective of prior anti-cancer therapy.…”
Section: Discussionmentioning
confidence: 53%
“…To remove this surface-attached ZIF-encased bacteria, we included three rapid washes with a low pH buffer—a method developed originally to strip IgE antibodies from cell surfaces. 97-99 This completely dislodged the ZIF bound to the macrophage surface as confocal micrographs show no CFT@ZIF on the surface of the acid-washed macrophages ( Fig. S2C ).…”
Section: Resultsmentioning
confidence: 99%
“…To remove this surface-attached ZIF-encased bacteria, we included three rapid washes with a low pH buffer-a method developed originally to strip IgE antibodies from cell surfaces. [100][101][102] Another LDH assay was conducted to ensure that the low pH wash would not be toxic to the RAW 264.7 macrophages, which again showed the treatment did not kill the cells (Fig. S5E).…”
Section: Vaccination With Cft@zif Induces a Robust Igg Responsementioning
confidence: 99%
“…While this initially appeared to validate prior literature observation, upon closer inspection, we found a significant amount of the CFT@ZIF had adhered to the surface of the macrophages. To remove this surface-attached ZIF-encased bacteria, we included three rapid washes with a low pH buffera method developed originally to strip IgE antibodies from cell surfaces. Another LDH assay was conducted to ensure that the low pH wash would not be toxic to the RAW 264.7 macrophages, which again showed the treatment did not kill the cells (Figure S5E). The low pH wash completely dislodged the ZIF bound to the macrophage surface as confocal micrographs show no CFT@ZIF on the surface of the acid-washed macrophages (Figure S5F).…”
Section: Results and Discussionmentioning
confidence: 99%